Embryonal tumors with multilayered rosettes, C19MC-altered or not elsewhere classified: Clinicopathological characteristics, prognostic factors, and outcomes of 17 children from 2018 to 2022 - Xu, Kailun; Sun, Zhaoyun; Wang, Lifeng; Guan, Wenbin (Frontiers in Oncology, 2022)
Objective: Embryonal tumors with multilayered rosettes (ETMRs) are a histologically heterogeneous entity and gather embryonal tumors with abundant neuropil and true rosettes (ETANTRs), ependymoblastoma, and medulloepithelioma. ETMRs are highly aggressive and associated with poorer clinical courses. However, cases of this entity are rare, and advances in molecular genetics and therapy are minor. The purpose of our study was to retrospectively analyze the clinical, pathological features, and prognostic factors of ETMRs. Methods: Our cohort consisted of 17 patients diagnosed with ETMRs in our hospital from 2018 to 2022, and two of them were lost to follow-up. Clinical data were retrieved, and immunohistochemistry and genetic analyses were performed. Results: Among 17 cases, 16 tumors were ETANTRs, and one was medulloepithelioma. Morphologically, tumor cells of ETANTRs could transform into anaplasia and lose the biphasic architecture during tumor progression. Immunohistochemistry of LIN28A revealed positive expression in 17 cases, and the expression of LIN28A was more intense and diffuse in the recurrent lesions than in primaries. The incidence of metastatic disease was 100% in patients aged > 4 years and 18% in the younger group. For patients receiving chemotherapy, the median overall survival time was 7.4 months, while that of those who didn’t receive it was 1.2 months. Nevertheless, surgical approaches, radiotherapy, age at presentation, gender, tumor location, and metastatic status were not associated with independent prognosis. Conclusion: ETANTR might not present as the typical morphologies during tumor progression, so analyses of C19MC amplification and Lin28A antibody are indispensable for diagnosing ETMRs accurately. Children aged > 4 years tend to have a higher rate of metastasis in ETMRs. Chemotherapy is the only prognostic factor for ETMRs patients with a favorable prognosis.